Learners’ Satisfaction and Academic Performance in Open and Distance Learning (ODL) Universities in Malaysia. - Jegathesan, Rajadurai; Noryati, Alias; Amar Hisham, Jaafar; Wan Nordiana, Wan Hanafi (2018)
Purpose: The focus of this paper is to identify learners’ satisfaction and performance levels in an online learning environment at the Open and Distance Learning (ODL) universities in Malaysia. Design/methodology/approach: 2283 valid questionnaires were completed by three batches of undergraduates. The responses revealed a significant correlation between the learners’ performance and satisfaction with the learning materials, assessment management, academic facilitation, the services provided by the universities and the promptness of their responses. The stepwise regression analysis indicated that services and assessment management significantly influenced learner performance. Findings: All the independent variables had means between 3.210 and 3.647. This indicates that the learners were satisfied with their usage of learning materials, assessment management, academic facilitation and the services provided by the universities. However, only two variables were related to learners’ performance, namely assessment management and services rendered by the universities. Research limitations/implications: Future studies should consider the inclusion of other variables such as the availability of alternative modes of enquiry and refining the items use to measure the variable in this study. The study could also engage a longitudinal method of data collection and be administered on a broader population involving all faculties and program levels. Practical implications: This study suggests to policy makers and academic leaders that they should continue to provide the current excellent level of support in the form of resources and services but they need to find creative ways to engender better performances by their learners. Originality/value: Earlier models of distance education used to be centered on correspondence courses, audio-based courses and video-taped lectures. These models are being updated with internet or computer based models. Consequently, there are different challenges in the delivery of ODL programs today. Hence, a learner’s demonstrated success in a conventional delivery may not adequately predict his or her success in an ODL program. Understanding the performance of present day ODL programs’ success factors will allow new ODL universities, or brick and mortar universities in the process of transforming to blended learning, undertake the necessary steps to ensure the success of their ODL programs.